High‐resolution simulation of B0 field conditions in the human heart from segmented computed tomography images. (26th April 2022) - Shang, Yun; Theilenberg, Sebastian; Terekhov, Maxim; Mattar, Wolfram; Peng, Boyu; Jambawalikar, Sachin R.; Schreiber, Laura M.; Juchem, Christoph
Abstract : B0 inhomogeneity leads to imaging artifacts in cardiac magnetic resonance imaging (MRI), in particular dark band artifacts with steady‐state free precession pulse sequences. The limited spatial resolution of MR‐derived in vivo B0 maps and the lack of population data prevent systematic analysis of the problem at hand and the development of optimized B0 shim strategies. We used readily available clinical computed tomography (CT) images to simulate the B0 conditions in the human heart at high spatial resolution. Calculated B0 fields showed consistency with MRI‐based B0 measurements. The B0 maps for both the simulations and in vivo measurements showed local field inhomogeneities in the vicinity of lung tips with dominant Z3 spherical harmonic terms in the field distribution. The presented simulation approach allows for the derivation of B0 field conditions at high spatial resolution from CT images and enables the development of subject‐ and population‐specific B0 shim strategies for the human heart. Abstract : A B0 simulation approach has been proposed to simulate high‐resolution B0 conditions in the human heart based on a magnetic susceptibility map derived from CT images. The proposed B0 simulation approach can efficiently investigate the B0 conditions in the human heart at a population level and paves the way to develop an optimized B0 shim strategy for cardiac MRI.